Modelling self-heating and thixotropy phenomena under the cyclic loading of asphalt. (8th May 2017) - Riahi, Ebrahim; Allou, Fatima; Botella, Ramon; Fakhari Tehrani, Fateh; Dubois, Frédéric; Absi, Joseph; Petit, Christophe; Pérez-Jiménez, Felix E.
Abstract : Asphalt concrete is a heterogeneous material containing a viscoelastic bituminous matrix and elastic aggregates. When testing asphalt materials under cyclic loading, various phenomena (so-called biasing effects) can decrease the modulus. This effect has been explained by an increase in the temperature of materials due to energy dissipation (self-heating), thixotropy and damage. The aim of this study is to analyse a uniaxial cyclic tension-compression test performed on bitumen and asphalt mixes, in modelling self-heating as one of the biasing effects. To quantify the self-heating and dissipated energy (as a heat source), a heterogeneous thermomechanical approach is introduced by separating the viscoelastic bituminous matrix from the elastic aggregates. According to this approach, various processes such as energy dissipation in the matrix due to viscoelastic properties, the thermal sensitivity of the matrix as well as its capacity to develop a heat source and diffuse heat through aggregates can all be studied. Local temperature variations are calculated by considering the heterogeneous dissipated energy field as a heat source. The complex modulus variation can then be calculated by taking into account both the temperature field and thermal sensitivity of the material. Simulation results show that as opposed to bitumen, in which 100% of complex modulus variations observed during a strain sweep test are due to self-heating, the results on asphalt mixes indicate that thixotropy varies with mechanical properties to a greater extent than self-heating. This fact is probably correlated with a higher strain level in thin bituminous matrix films, a higher load velocity in thin matrix films, material heterogeneity, and the 3D characteristic of matrix loading during the tension-compression test on asphalt mixes.